REGINE : regularisations in Europe - Baldwin-Edwards, Martin, 1956-; Kraler, Albert (Pallas Publications, 2009)
A thourough investigation of possible rationales for regularisation, its impact, and the relationship of regularisation to the wider policy framework on migration and asylum.